Genetic Diagnosis of Dysplasminogenemia: Detection of an Ala601 -Thr Mutation in 118 out of 125 Families and Identification of a New Asp676-Asn Mutation - Tsutsumi, Seiji; Saito, Tetsuo; Sakata, Toshiyuki; Miyata, Toshiyuki; Ichinose, Akitada (Thrombosis and Haemostasis, 1996)
Dysplasminogenemia (plasminogen abnormality) is frequently found in association with thrombosis. Two types of mutation, Ala601-Thr and Val355-Phe, have already been identified; the precise genetic defects of most of these patients, however, remain unknown. In this study, we examined the genetic DNAs of two unrelated cases by single-strand conformational polymorphism and nucleotide sequencing analysis. A new mutation, designated as Asp676-Asn, has been identified in these cases. This mutation leads to the loss of a negatively-charged residue and the creation of a potential carbohydrate attachment site, which may impair the enzymatic properties of plasminogen. As many as 158 individuals with dysplasminogenemia were analyzed by a combination of in vitro amplification and restriction digestion. Among 125 unrelated families, the Ala601-Thr mutation accounted for about 94% of cases. The Val355-Phe mutation was found in four unrelated families, indicating that it is a recurring mutation and is not very rare.